Exercise-induced anxiety impairs local and systemic inflammatory response and glucose metabolism in C57BL/6J mice - I. Gálvez; M.C. Navarro; S. Torres-Piles; L. Martín-Cordero; M.D. Hinchado; E. Ortega (Brain, Behavior, & Immunity - Health)
Introduction: The complex physiological and psychological responses to regular exercise are yet to be fully elucidated. Exercise strongly modulates the immune system, inducing a plethora of dynamic responses involving the innate immune cell function and inflammatory processes that contribute to both potential health benefits and harmful side effects. Indeed, the relationship between physical exercise, stress, immunity, and metabolism serves as a paramount model of neuroimmunoendocrine interaction. Thus, the objective of this study was to conduct a comprehensive analysis of both systemic and local immunophysiological responses together with behavioral responses to a protocol of anxiety-inducing exercise. Material and methods: C57BL/6J mice were randomly allocated into sedentary or exercised groups, where the anxiety-inducing exercise protocol was based on a 14-day consecutive program of swimming in water at 38 °C. Anxiety-like behavior was corroborated through the elevated plus maze test. Systemic biomarkers of the stress response were assessed using ELISA technique and the expression of systemic inflammatory cytokines with Bio-Plex system. Phagocytic/microbicide activity, the expression of M1/M2 phenotype markers (CD11c, iNOS, CD206, ARG-1) and cytokines of the inflammatory response (MCP-1, IL-8, IL-6, TNF-α, TGF-β, IL-10) of peritoneal macrophages were determined via flow cytometry. Adipose tissue macrophage infiltration was studied through fluorescence immunohistochemistry. Results: Anxiety-like behavior, elevated circulating glucose concentrations, systemic stress and inflammatory responses, together with increased oxidative stress and inflammatory profile of peritoneal macrophages, and macrophage infiltration in white adipose tissue were observed in exercised animals. Conclusions: A protocol of exercise that induces anxiety is associated with a neuroimmunoendocrine dysregulation affecting the feedback between the inflammatory and the stress responses, together with detrimental metabolic effects in glucose modulation. Systemic inflammatory alterations are accompanied by detrimental inflammatory responses in tissue macrophage populations. Altogether, these results show that exercise associated with anxiety, stress, pro-inflammatory responses, and hyperglycaemia represents a model of ‘dangerous exercise’.